Endothelial nitric oxide synthase dimerization is regulated by heat shock protein 90 rather than by phosphorylation. - Weiguo Chen; Hongbing Xiao; Alicia N Rizzo; Wei Zhang; Yifeng Mai; Meng Ye (PLoS ONE, 2014)
Endothelial nitric oxide synthase (eNOS) is a multifunctional enzyme with roles in diverse cellular processes including angiogenesis, tissue remodeling, and the maintenance of vascular tone. Monomeric and dimeric forms of eNOS exist in various tissues. The dimeric form of eNOS is considered the active form and the monomeric form is considered inactive. The activity of eNOS is also regulated by many other mechanisms, including amino acid phosphorylation and interactions with other proteins. However, the precise mechanisms regulating eNOS dimerization, phosphorylation, and activity remain incompletely characterized. We utilized purified eNOS and bovine aorta endothelial cells (BAECs) to investigate the mechanisms regulating eNOS degradation. Both eNOS monomer and dimer existed in purified bovine eNOS. Incubation of purified bovine eNOS with protein phosphatase 2A (PP2A) resulted in dephosphorylation at Serine 1179 (Ser1179) in both dimer and monomer and decrease in eNOS activity. However, the eNOS dimer∶monomer ratio was unchanged. Similarly, protein phosphatase 1 (PP1) induced dephosphorylation of eNOS at Threonine 497 (Thr497), without altering the eNOS dimer∶monomer ratio. Different from purified eNOS, in cultured BAECs eNOS existed predominantly as dimers. However, eNOS monomers accumulated following treatment with the proteasome inhibitor lactacystin. Additionally, treatment of BAECs with vascular endothelial growth factor (VEGF) resulted in phosphorylation of Ser1179 in eNOS dimers without altering the phosphorylation status of Thr497 in either form. Inhibition of heat shock protein 90 (Hsp90) or Hsp90 silencing destabilized eNOS dimers and was accompanied by dephosphorylation both of Ser1179 and Thr497. In conclusion, our study demonstrates that eNOS monomers, but not eNOS dimers, are degraded by ubiquitination. Additionally, the dimeric eNOS structure is the predominant condition for eNOS amino acid modification and activity regulation. Finally, destabilization of eNOS dimers not only results in eNOS degradation, but also causes changes in eNOS amino acid modifications that further affect eNOS activity.